(untitled) (Harmoni, 2020)
The economic growth affects the rise of middle class, includes Muslim class. The increase of the middle-class Moslem affects religiosity in Surakarta City. This study aimed (1) to describe the religiosity of middle class Muslims in Surakarta City as the result of their interaction with globalism and modernism and (2) to identify the factors influencing the religiosity of that class. The study was conducted in Surakarta City using a qualitative approach. Data were collected through Focus Group Discussion (FGD) with 11 informants with various relevant backgrounds. Then those data were analyzed qualitatively and compared to relevant previous studies. The study resulted: (1) Middle-class Muslims in Surakarta City showed their religiosity by following Majelis Taklim that combining spiritual and social activities and it was different to conventional ones. Religiosity was presented in sharia lifestyle. This was confirmed through the middle classΓÇÖs appearances and preferences on Islamic-labelled products and services. On one hand, the interaction with modernism value and identity as the part of global Islamic ummah raised the spirit to purify Islamic value. Then, it potentially closed the middle class Muslims to radicalism. On the other hand, that interaction possibly trapped middle-class Muslim on the consumptive and hedonistic culture that contradicted to sharia values. (2) The factors that influenced middle-class MuslimΓÇÖs religiosity were financial stability, appropriate rationalistic ability, and Islamic learning media. Internet and social media provided crucial influences on the religiosity of middle-class Muslims in Surakarta city since they became the important media to understand Islam.